2003
DOI: 10.1152/ajpheart.00179.2003
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of mitral annular and leaflet muscle: effects on annular and leaflet dynamics

Abstract: Miller, and Neil B. Ingels, Jr. Ablation of mitral annular and leaflet muscle: effects on annular and leaflet dynamics. Am J Physiol Heart Circ Physiol 285: H1668-H1674, 2003 10.1152/ajpheart.00179.2003 and leaflet three-dimensional (3-D) dynamics were examined after circumferential phenol ablation of the MA and anterior mitral leaflet (AML) muscle. Radiopaque markers were sutured to the left ventricle, MA, and both mitral leaflets in 18 sheep. In 10 sheep, phenol was applied circumferentially to the atrial su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…A key prediction of this hypothesis is that excitation can vary leaflet stiffness in the closed valve. 2) Leaflet excitation develops a brief twitch contraction to aid valve closure (7,32,33,41). A key prediction of this hypothesis is that leaflet stiffness is transiently increased during valve closure.…”
mentioning
confidence: 99%
“…A key prediction of this hypothesis is that excitation can vary leaflet stiffness in the closed valve. 2) Leaflet excitation develops a brief twitch contraction to aid valve closure (7,32,33,41). A key prediction of this hypothesis is that leaflet stiffness is transiently increased during valve closure.…”
mentioning
confidence: 99%
“…annular physiology; ventricular long-axis function; echocardiography; three dimension; four dimension THE MITRAL ANNULUS (MA) is a discontinuous fibrous ring and an essential component of the mitral valve/left atrial/left ventricular (LV) complex. It contributes to efficient valve closure as well as unimpeded LV filling (14,19,28,29). Many studies support the concept that the motion of the MA is dynamic throughout the cardiac cycle, yet the timing and extent of annular motion and shape variation remain incompletely understood (28,29).…”
mentioning
confidence: 99%
“…Finally, Timek et al (15) showed that ablation of leaflet myocytes in the annular region of the ovine anterior mitral leaflet slowed valve closure by some 35 ms relative to controls. This has been interpreted to suggest that the leaflet twitch may help close the valve, as suggested as a possibility by Curtis and Priola (3).…”
Section: Discussionmentioning
confidence: 99%
“…markers; stiffness MITRAL VALVE CLOSURE MAY BE aided by a brief contraction of myocytes in the annular third of the anterior leaflet (AL) (15). This contraction is also believed to be the cellular basis for the substantial AL stiffening observed during isovolumic contraction (IVC) (5).…”
mentioning
confidence: 99%